Answer:
[tex]c = -\frac{5}{3}[/tex]
Step-by-step explanation:
Given equation,
[tex]-3-\frac{3}{4}(c-4) = \frac{5}{4}[/tex]
By addition property of equality,
[tex]-\frac{3}{4}(c-4)=\frac{5}{4}+3[/tex]
By distributive property,
[tex]-\frac{3}{4}c+3=\frac{5+12}{4}[/tex]
By subtraction property of equality,
[tex]-\frac{3}{4}c=\frac{17}{4}-3[/tex]
[tex]-\frac{3}{4}c=\frac{17-12}{4}[/tex]
[tex]-\frac{3}{4}c=\frac{5}{4}[/tex]
By cross multiplication,
[tex]-3c=5[/tex]
By division property of equality,
[tex]\implies c = -\frac{5}{3}[/tex]
Hence, the value of c is [tex]-\frac{5}{3}[/tex]